Lectotypification of the Linnaean name Centaurea montana (Compositae, Cardueae-Centaureinae) - Alti̇nordu, Fahim; Susanna, Alfonso (Phytotaxa, 2017)
A lectotype is designated for the Linnaean name Centaurea montana from the original material conserved in the Burser herbarium (UPS).